Computer Methods in Biomechanics and Biomedical Engineering Proceedings of the 14th International Symposium CMBBE, Tel Aviv, Israel, 2016 (Lecture Notes in Bioengineering,, 2018)
This edited volume collects the research results presented at the 14th International Symposium on Computer Methods in Biomechanics and Biomedical Engineering, Tel Aviv, Israel, 2016. The topical focus includes, but is not limited to, cardiovascular fluid dynamics, computer modeling of tissue engineering, skin and spine biomechanics, as well as biomedical image analysis and processing. The target audience primarily comprises research experts in the field of bioengineering, but the book may also be beneficial for graduate students alike.